A State Synchronization Mechanism for Orchestrated Processes - Lei Wang; Wombacher, A.; Pires, L. F.; van Sinderen, M. J.; Chihung Chi (2012 IEEE 16th International Enterprise Distributed Object Computing Conference, 2012)
Two orchestrated processes interacting with each other have to maintain their own states. Messages are used to synchronize states between orchestrated processes. Server crash and network failure may result in loss of messages and therefore result in a state change performed by only one party. Thus, the states of the parties are no longer synchronized, resulting in state inconsistencies and in worst case deadlocks. In this paper, we propose a mechanism for guaranteed state synchronization of orchestrated processes with system and network failures. Our mechanism is based on interaction patterns and process transformations. The basic idea is to redesign the original processes into their state synchronization-enabled counterparts via process transformations that can be automated. The transformation mechanism is formalized based on Colored Petri Nets. We present the formal proof of the correctness of our mechanism and give the overhead analysis to illustrate its practicability.